150 If an Agatston Score of Zero Means Neither Absence of Coronary Calcium nor Absence of Significant Disease, Should we be Following Nice Clinical Guidance 95?. (31st May 2014) - Smith, David; Routledge, Helen; Karunasaargarar, Kavita; Sayers, Max; Ahmad, Imran
Abstract : Introduction: NICE Clinical Guidance 95 (March 2010) lays out a pathway for the investigation of chest pain incorporating more modern imaging modalities now spreading to most institutions. It suggests the use of CT calcium scoring to investigate those deemed to be low risk (10–29%) and states no other investigation is necessary (including proceeding to CT coronary angiography (CTCA)) if the agatston score (AgSc) is 0. This is despite evidence suggesting such patients will have a significant incidence of >50% coronary stenosis. Methods: This prompted us to perform a retrospective audit of all coronary CT scans performed in the preceding 2 years at our institution ( where we routinely proceed to CTCA after calcium scoring ) for the investigation of chest pain (n = 168). We also surveyed British centres performing CTCA asking firstly whether they only scan those at low risk and secondly whether they continue with CTCA even if the agatston score is 0. Results: 88 (52%) of patients had an agatston score of 0. 5 (5.6%) of those had a significant (>50%) coronary lesion. This compares with 3.5% in the CONFIRM trial. One such patient with a pretest probability of 21% is shown in Figure 1 . CT coronary angiogram and corresponding invasive angiographic images demonstrate severe lesions of right and left anterior descending arteries. It also demonstrates another interesting point: Although the agatston score was zero, there are smaller deposits of calcium obvious on the CTCA images of the LAD. This is due to limitations inherent in all scanners. Thus, a negative agatston score does not mean the absence of calcium. Only 2 of 21 centres (9.5%) were adhering to the guidance in scanning only those truly at low risk and not proceeding to CTCA if the agatston score is zero. Some cited the fact their newer modern scanners deliver a similar radiation dose to perform CT coronary angiography as for a coronary calcium score. Conclusions: In real life, the use of CTCA is not confined to low risk patients. This may be driven by resources. The lack of availability of relatively time-consuming non-invasive stress imaging may mean that a relatively quick CT scan absorbs a proportion of the intermediate risk cohort. This shifting of goalposts may translate into an increased incidence of significant disease in the CT-scanned group, as in our cohort. The overall implication is that as cardiac CT continues to be taken up by more and more centres across the UK, more patients with significant underlying coronary disease risk being missed if this aspect of CG95 is strictly followed.